Social isolation as a risk factor for inadequate diet of older Eastern Europeans - Kalousova, Lucie (International journal of public health, 2014)
OBJECTIVES: Social isolation has been shown to be a risk factor for inadequate diet among older adults living in Western Europe and North America. This article investigates whether socially isolated older adults (65+) living in Eastern Europe also experience an increased risk of dietary inadequacy. METHODS: The study used SHARE IV survey data collected in the Czech Republic (n = 2,867), Poland (n = 772), and Hungary (n = 1,353). Logistic regression models were estimated for each country separately to predict the likelihood of two proxies for dietary adequacy, having three meals a day and/or a serving of fruits or vegetables, by social isolation. RESULTS: Social isolation was associated with lower likelihood of having three meals a day among Czech older adults (OR 0.39) and with lower likelihood of having a daily serving of fruits or vegetables among Czech (OR 0.62) and Polish older adults (OR 0.35). No association between social isolation and either one of the outcomes was found in Hungary. CONCLUSIONS: Socially isolated Eastern European older adults may be at a higher risk of dietary inadequacy, particularly in the Czech Republic and Poland.
Keywords: logistické modely; průzkumy a dotazníky; Female; Social Isolation; ženské pohlaví; Logistic Models; Malnutrition; Surveys and Questionnaires; Diet Surveys; lidé; sociální izolace; podvýživa; Aged, 80 and over; dieta; Humans; Risk Factors; Diet; Male; dieta - přehledy; Aged; Czech Republic; Socioeconomic Factors; rizikové faktory; Hungary; Česká republika; senioři nad 80 let; socioekonomické faktory; senioři; mužské pohlaví; Maďarsko; Poland; Polsko